Pengaruh Keberhasilan Rejuvinasi Terhadap Pertumbuhan Vegetatif Kopi Robusta Klon BP 409 dan BP 534 - Handayani, Hatmiyarni Tri; Hartatie, Dian; Setyoko, Ujang; Hudori, Huda Ahmad (Jurnal Ilmiah Inovasi, 2025)
Rejuvination is a rejuvenation pruning that is carried out to improve the quality of coffee plants that are old and no longer productive. This study aims to determine the success of rejuvation in BP 409 and BP 534 clone robusta coffee plants with a 100% pruning system (trimming-unpruning). The rejuvenated plants were then observed including the tallest stem, the longest primary branch, and the number of leaf segments (tides). The results showed that the BP 409 clone grew better than BP 534. The measurement results show that BP 409 has the highest value in all three parameters, while the BP 534 clone has the lowest value in all three parameters. The highest stem reaches 136 cm and the lowest reaches 71 cm. The longest primary branch reaches 80 cm and the shortest is 57 cm. The highest number of leaf segments was 177 pairs and the lowest was 84 pairs. Rejuvination activities can be said to be successful by looking at the data obtained from the research results.